Analisis Waiting Time dalam Proses Perakitan MV Switchgear dengan Lean Production - R. Pitaloka Naganingrum; Lobes Herdiman (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
PT. Siemens Indonesia is an industry engaged in the production of Energy Distribution, as Simoprime World Panel with world market-oriented. The problems that occurred there was delay time and completion of the scheduled production target. Delay in completion of the scheduled deadline because of the inefficiency caused by the flow process in the handling of waste resulting from the assembly. The purpose of this study was to identify waste and operating conditions that occurred on the main assembly. Lean Production was used in this research. In lean production concept, Value Stream Analysis Tool (VALSAT) was used as an instrument to map the waste that occurred and detailed Mapping Tool to determine the operating conditions. In identifying waste, the weighting of each work station waste in the main assembly. Based on the weighting of waste which made known that the biggest waste of waiting time and for the operating conditions, 21% non value adding activities from main assembly.